1999
DOI: 10.1046/j.1365-2923.1999.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of student-generated learning issues on individual study time and academic achievement

Abstract: Students in a problem-based curriculum seem to become better self-directed learners during the years of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 9 publications
5
33
0
1
Order By: Relevance
“…Graduates of PBL courses do not seem to be any better, or any worse, doctors than graduates from other courses. [23][24][25][26][27][28][29] A curriculum delivered in one school may provide quite different learning experiences from a similar-looking curriculum in another school. The clinical environment, attitudes of teachers, modes of assessment, peer support and other contextual factors will influence students' learning experiences.…”
Section: How Do Students Learn?mentioning
confidence: 99%
“…Graduates of PBL courses do not seem to be any better, or any worse, doctors than graduates from other courses. [23][24][25][26][27][28][29] A curriculum delivered in one school may provide quite different learning experiences from a similar-looking curriculum in another school. The clinical environment, attitudes of teachers, modes of assessment, peer support and other contextual factors will influence students' learning experiences.…”
Section: How Do Students Learn?mentioning
confidence: 99%
“…However, they mainly focused on the problem analysis and/or the reporting phase as it is not possible to observe how students learn during their extended self-directed study time in a naturalistic environment. Studies on the learning activities and processes during self-directed study time inevitably relied on self-report (Dolmans et al 1995;Van den Hurk et al 1999). Self-reports however, tend to reconstruct activities from memory, hence limiting their validity.…”
Section: Introductionmentioning
confidence: 99%
“…Results from this study confirmed and added support to the earlier findings on the importance of the quality of problems. Probing further, van den Hurk, Wolfhagen, Dolmans, and van der Vleuten (1999) investigated the influence of the quality of problems and tutorial group processes (e.g., breadth and depth of discussion in the tutorial group) on generation of useful learning issues. They found that the quality of the problems indeed had an influence on the generation of useful learning issues.…”
mentioning
confidence: 99%